Research on the Treatment of Chronic Pulmonary Heart Disease with Traditional Chinese Medicine in Recent 10 Years based on CiteSpace Visual Analysis - Zhai, Yu; Liu, Yishu (Journal of Contemporary Medical Practice, 2024)
Objective: To investigate the development regularity, research status and future research hotspots of chronic pulmonary heart disease treated with traditional Chinese medicine (TCM) in recent 10 years by visual analysis of CiteSpace software. Methods: The relevant literatures on the treatment of chronic pulmonary heart disease with traditional Chinese medicine published from 2014 to 2023 in the CNKI database were searched, and the number of documents issued, authors, institutions, and keywords of the included literatures were analyzed using CiteSpace software, and the knowledge map was drawn. Results: After screening, 683 articles were included and 262 authors were included, and Jun Liu and Zhengping Bai were the authors with the largest number of documents issued; A total of 244 research institutions were included, represented by Hunan University of Traditional Chinese Medicine; through co-occurrence analysis of keywords, the frequency of efficacy was the highest; keywords were clustered to form a total of 10 cluster labels; To highlight the keywords, cardiopulmonary function is always a research hotspot in this field, and quality of life, acupoint application, medication rules, and data mining may be future research hotspots in this field. Conclusion: At present, the research on the treatment of cor pulmonale with traditional Chinese medicine is in the bottleneck stage. It is recommended that researchers and institutions strengthen cooperation, carry out high-quality research, give play to the advantages of the motherland medicine, and promote the development of traditional Chinese medicine in this field.